Vision System for Autonomous Underwater Vehicle Using Wireless Camera for Monitoring and Surveillances Application - Mohd Aras, Mohd Shahrieel; Md Basar, Mohd Farriz (2009)
This paper present the new design of vision system for autonomous underwater vehicle with the implementation of wireless camera, whereby, produce clearer image. The major obstacle faced by underwater vision system is the extreme loss of color and contrast when submerged to any significant depth whereby the image quality produced is low. Therefore, as to obtain clearer images, several investigations will be done in order to know the appropriate distance required between the images with the camera. At the end of the project, the new design of the vision system will be well functioned and can be applied to capture clearly the underwater images and also might be used to explore the nature of underwater. This new vision system also could be used for monitoring, surveillances, and maintenance tasks for underwater where it is risky for the human to work in it.